Pengaruh Pelatihan, Disiplin Kerja dan Jenjang Karir Teradap Kinerja Karyawan - Indra Kurniawan; Tika Nirmala Sari (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine and analyze the effect of Training, Work Discipline, and Career Path on Employee Performance at PT Capella Dinamik Nusantara, SM. Raja Branch. This research is classified as associative research and employs a quantitative method. The population in this study consists of all employees of PT Capella Dinamik Nusantara, SM. Raja Branch, the exact number of which is unknown. The sampling technique used was non-probability sampling with a saturated sampling approach. The total sample taken in this study amounted to 64 respondents, with the distribution of questionnaires focused on all employees of PT Capella Dinamik Nusantara, SM. Raja Branch The results of the study indicate that Training has a positive and significant partial effect on Employee Performance, Work Discipline has a positive and significant partial effect on Employee Performance, and Career Path also has a positive and significant partial effect on Employee Performance. Simultaneously, Training, Work Discipline, and Career Path have a positive and significant effect on Employee Performance. The adjusted R square value of 0.721 can be referred to as the coefficient of determination, meaning that 72.1% of the variation in Employee Performance can be explained by Training, Work Discipline, and Career Path, while the remaining 27.9% which is not scrutinized.